An environmental sustainability assessment of China's cement industry based on emergy. (January 2017) - Zhang, Xiaohong; Shen, Jianming; Wang, Yanqing; Qi, Yan; Liao, Wenjie; Shui, Wei; Li, Li; Qi, Hui; Yu, Xiaoyu
Highlights: The emergy evaluation of China's cement industry was implemented. Mineral resources have absolute contribution to this industry. Coal is the main energy source for this industry. This industry has relatively weak competition ability. This industry is not sustainable in the long run due to high environmental load. Abstract: As one of important building materials, the sustainability of cement production is widely concerned in the world. This research evaluated the sustainability of China's cement industry in 2010 using emergy analysis. Several emergy based indicators were adopted to describe the comprehensive performance of this system from different angles, including Percentage of renewability (%R), Unit emergy value (UEV), Emergy yield ratio (EYR), Emergy exchange ratio (EER), Environmental load ratio (ELR) and Emergy sustainable index (ESI). The research results show that (1) Mineral resources have absolute contribution to China's cement production; (2) Coal is the main energy source for China's cement industry; (3) China's cement industry has relatively weak competition ability due to relatively high ratio of purchased inputs; (4) China's other industries have benefited greatly from this industry by exchanges; (5) China's cement industry cannot keep sustainable in the long run due to its high environmental load; (6) the UEV of Chinese cement in 2010 is 3.64E15 sej/t (based on the emergy baseline 15.83E24 sej/yr). Finally, the related policy implications are proposed from four aspects, including (1) Accelerating the adjustment of process structure and technical innovation; (2) Promoting the substitution of raw materials or fuels; (3) Raising the price of cement products; (4) Decreasing the export of cement products.